The metabolism and hormonal responses of human eccrine sweat glands isolated by collagenase digestion. - Kealey, T (1983)
1. Collagenase digestion of biopsies of human skin yields eccrine sweat glands that can be picked out under binocular light microscopy. The glands are viable as determined by the exclusion of Trypan Blue, the uptake of Methylene Blue, electron microscopy, the rate of lactate dehydrogenase release, ATP content and the rates of glucose oxidation and lactate release. 2. It is proposed that eccrine sweat glands engage in aerobic glycolysis, which accounts for the high content of lactate in sweat (15--60 mM) and the high lactate/pyruvate ratio (100: 1) [Emrich & Zwiebel (1966) Pfluegers Arch. 290, 315--319]. 3. Acetylcholine causes a 4-fold increase in cyclic GMP content, dilatation of the intercellular canaliculi and a reversible, atropine-sensitive, 2-fold increase in the rates of glucose oxidation and lactate release. 4. Isoprenaline causes a 2.5-fold increase in cyclic AMP content. Phenylephrine does not significantly alter cyclic nucleotide metabolism.